2022
DOI: 10.1002/smi.3192
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial safety climate and supportive leadership as vital enhancers of personal hope and resilience during the COVID‐19 pandemic

Abstract: This study aimed to investigate the effects of supportive leadership and psychosocial safety climate on personal hope and resilience among nurses during the pandemic. Conservation of resource theory was employed to explain the effects of psychosocial safety climate and supportive leadership on nurses' hope and resilience. A cross-sectional design was employed to collect data. Six-hundred and twenty-three nurses across 68 hospitals who were in direct contact with COVID-19 patients during the fifth wave of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…For instance, a study reported that the inverse relationship between PSC and depressive symptoms was stronger for females than males [ 36 ]. Moreover, a high PSC context makes workers more assertive [ 39 ] and resilient [ 40 ] and presents opportunities for hope [ 40 ]. We present thematic analysis of the influence of PSC on workplace mistreatment and mental health in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study reported that the inverse relationship between PSC and depressive symptoms was stronger for females than males [ 36 ]. Moreover, a high PSC context makes workers more assertive [ 39 ] and resilient [ 40 ] and presents opportunities for hope [ 40 ]. We present thematic analysis of the influence of PSC on workplace mistreatment and mental health in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Resilient workers can effectively cope with setbacks, learn from experiences, and develop strategies to navigate through adversity, ultimately promoting their overall well-being and ability to thrive. [ 40 ] Hope Hope is an optimistic and positive state of mind characterised by the belief that things can improve or desired outcomes can be achieved. It involves having confidence, aspirations, and a sense of possibility for the future, even in challenging circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…environment(Park & Jang, 2022). For example,Siami et al (2023) confirmed that a psychological safety climate and supportive leadership are positively associated with personal psychological resilience.Öksüz et al (2019) also found that the nurses with greater perceived family support demonstrated higher levels of psychological resilience. Furthermore, the results of this study showed that the psychological resilience of most nurses needed to be improved.The group with high psychological resilience (Profile 3) accounted for 20% of the total sample.…”
mentioning
confidence: 75%
“…Psychological resilience was able to be developed through a supportive environment (Park & Jang, 2022). For example, Siami et al (2023) confirmed that a psychological safety climate and supportive leadership are positively associated with personal psychological resilience. Öksüz et al (2019) also found that the nurses with greater perceived family support demonstrated higher levels of psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…A good PSC has been associated with better managerial practices because it promotes better mental health for managers ( Biron et al, 2018 ; Parent-Lamarche and Biron, 2022 ). In the same vein, a multi-level study of healthcare workers during the pandemic showed that PSC promotes resilience through hope, as well as increasing the impact of supportive leadership on employee hope ( Siami et al, 2022 ). In contrast, when PSC is low, the means available to employees to report their difficulties may be inadequate or non-existent.…”
Section: Introductionmentioning
confidence: 99%